Patient delay in acute myocardial infarction: a long journey still ahead. (3rd October 2022) - Marques, C; Cabrita, A; Maia Araujo, P; Proenca, T; Pinto, R; Carvalho, M; Costa, C; Amador, A F; Calvao, J; Pinho, A; Oliveira, C; Santos, L; et al.
Abstract: Background: It is overly known that time delays in acute myocardial infarction (AMI) strongly influence its outcomes. Patient delay (PD) is repeatedly pointed out as the longer one in this context, as well as it is the less modifiable one by organizational measures. Therefore, it is crucial to understand the reasons for longer PD in our population, to define proper strategies to improve PD and, ultimately, AMI-outcomes. Methods: In this six-month prospective study of patients (pts) admitted in a tertiary hospital due to type-1 AMI, 194 pts were consecutively enrolled between May and October 2021. Data was based on a pts well-structured interview within 48h after admission and review of medical records. Results: Our work spotted several aspects significantly influencing PD in AMI context (Figure 1). Concerning pts cardiovascular background, a trend towards a shorter PD was found in pts with at least one cardiovascular risk factor (CVRF) (p=0, 08) and with a previous history of AMI (p=0, 08). Regarding clinical presentation, a significantly shorter PD was found in pts presenting with associated symptoms (p=0, 02), higher chest pain intensity (chest pain intensity ≥7 vs <7 in a 0–10 scale; p=0, 03) and symptoms onset on weekdays rather than weekends (p=0, 003). Regarding pts knowledge, significant differences were found when pts recognized their symptoms as AMI, presenting a shorter PD in this context (p=0, 006). Curiously, pts ability to correctly identify AMI symptoms, when asked, or to acknowledge their CVRF (when present), did not influence PD. Considering sociodemographic factors, higher incomes (p=0, 03) and non-rural residence (p=0, 03) significantly translated into shorter PD. No differences were found in PD according to pts age, gender or educational level. After this initial univariate analysis, multiple linear regression was performed to identify possible predictors of PD. Four variables were identified: pts ability to recognize their symptoms as AMI (β −0.199; 95% CI: −277 to −34, 87; p=0.012), living in a non-rural residence (β 0.154; 95% CI: 0.12–161.44; p=0.05), presenting associated symptoms (β −0.194; 95% CI: −257.43 to −28.84; p=0.014) and occurrence of symptoms on weekdays (β 0.170; 95% CI: 12.73–259.49; p=0.031) predicted shorter patient delays. Conclusion: Our study clearly points to the need for increasing public awareness and educational measures, mainly in pts living in rural areas, in order to: 1) Improve pts knowledge about AMI symptoms, clarifying that atypical symptoms can happen; 2) Reinforce the importance of shortening AMI time delays, clearly explaining the concept "time is muscle". Funding Acknowledgement: Type of funding sources: None.